PUBLIC POLICY STRATEGY FOR THE REGIONAL SECRETARIAT OF THE CITY OF TASIKMALAYA SUNDAWA BAHTIAR - Sundawa Bahtiar (Sean Institute, 2022)
Public policies are decisions made, proposed by individuals, groups or by the government itself in an effort to resolve various problems that arise to find a way out through ways or steps to solve them. Policies are made to solve various problems encountered, and when policies do not achieve the desired results, policies present themselves as solutions. This study uses a qualitative method with the aim that there is greater spontaneity and better adaptation of the interaction between researchers and research sources in obtaining answers to research questions. The results of this study explain that public policy is basically closely related to government regulations, where government policies are often criticized by the community, because in a decision sometimes it makes people or certain groups feel uncomfortable and disturbed, even though a policy has good and perfect goals. Public policy itself is often considered as a binding distribution of power values for all societies. The current government is required to create high-performance, clean, effective, efficient and accountable governance, and free from corrupt practices, collusion and nepotism. This is an obligation that must be realized by the current government. As in the government environment, the regional secretariat of Tasikmalaya City can be assessed through the factors of effectiveness, efficiency, adequacy, equity, responsiveness and relevance. Periodically, it is necessary to evaluate the achievement of the work results of employees and work units based on SOP-AP, so that obstacles can be identified in achieving the goals and targets that have been set and developing employees to increase knowledge, work skills and improve skills through formal education and appropriate education and training. organized by other institutions.